2017
DOI: 10.1002/anie.201702417
|View full text |Cite
|
Sign up to set email alerts
|

AgHalo: A Facile Fluorogenic Sensor to Detect Drug‐Induced Proteome Stress

Abstract: Drug-induced proteome stress that involves protein aggregation may cause adverse effects and undermine the safety profile of a drug. Safety of drugs is regularly evaluated using cytotoxicity assays that measure cell death. However, these assays provide limited insights into the presence of proteome stress in live cells. A fluorogenic protein sensor is reported to detect drug-induced proteome stress prior to cell death. An aggregation prone Halo-tag mutant (AgHalo) was evolved to sense proteome stress through i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 47 publications
2
83
0
1
Order By: Relevance
“…This was accompanied by the detection of Hsp27 foci by IF that co‐localized with HSP27:GFP foci (Figure A vii–ix), demonstrating that HSP27 was recruited to the misfolded proteins accumulating in the cytoplasm. Upon transient transfection of a Hsp27‐GFP protein in HEK293T cells, cells treated with a proteome destabilizer also exhibited the formation of fluorescence puncta, similarly to our observations, confirming that Hsp27 is a global aggregation sensor at the cellular level. In addition to this, western blot analysis showed that both endogenous HSP27 and the HSP27:GFP sensor expression significantly increased after proteasome inhibition (Figure B).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This was accompanied by the detection of Hsp27 foci by IF that co‐localized with HSP27:GFP foci (Figure A vii–ix), demonstrating that HSP27 was recruited to the misfolded proteins accumulating in the cytoplasm. Upon transient transfection of a Hsp27‐GFP protein in HEK293T cells, cells treated with a proteome destabilizer also exhibited the formation of fluorescence puncta, similarly to our observations, confirming that Hsp27 is a global aggregation sensor at the cellular level. In addition to this, western blot analysis showed that both endogenous HSP27 and the HSP27:GFP sensor expression significantly increased after proteasome inhibition (Figure B).…”
Section: Resultssupporting
confidence: 87%
“…Also, Htt‐GFP sensors are used to study the impact of expanded polyglutamine (PolyQ) chains on protein aggregation and cell viability, which is relevant to characterize HD . More recently, a fluorogenic aggregation prone Halo‐tag mutant was developed and is a valuable tool to evaluate drug‐induced proteome stress …”
Section: Introductionmentioning
confidence: 99%
“…reported a conjugate of a chemical probe and a de novo designed enzyme, which formed fluorescent aggregates in the presence of cellular stress . A similar approach utilizing a fluorogenic probe targeting an aggregation‐prone “HaloTag” protein mutant has also been reported by the same group . Additionally, other methods that focus on cell lysate analysis have also been documented .…”
Section: Introductionmentioning
confidence: 84%
“…Halotag was modified to accommodate the environmentally sensitive dansyl moiety and it was shown that binding of various alkyl halides could quench the fluorogenic response. One of the most developed systems is a fluorogenic proteome‐stress sensor . To develop this sensor, an unstable Halotag mutant that is prone to aggregation was evolved.…”
Section: Using Fluorogenic Proteins To Develop Biosensors To Detect Imentioning
confidence: 99%